2019
DOI: 10.1016/j.neuroimage.2019.116107
|View full text |Cite
|
Sign up to set email alerts
|

Current progress in real-time functional magnetic resonance-based neurofeedback: Methodological challenges and achievements

Abstract: Neurofeedback (NF) is a research and clinical technique, characterized by live demonstration of brain activation to the subject. The technique has become increasingly popular as a tool for the training of brain self-regulation, fueled by the superiority in spatial resolution and fidelity brought along with real-time analysis of fMRI (functional magnetic resonance imaging) data, compared to the more traditional EEG (electroencephalography) approach. NF learning is a complex phenomenon and a controversial discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
125
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(137 citation statements)
references
References 122 publications
3
125
0
Order By: Relevance
“…However, we highlight the explorative fashion of this finding and we stress that only the original data showed significant reductions. Nonetheless, our results are in line with a recent study showing that amygdala electrical fingerprint neurofeedback resulted in a larger reduction of alexithymia scores compared to a control group (Keynan et al, 2019). Conversely, neurofeedback studies to increase the amygdala response showed that the ability to identify or describe one's own emotions (as indicated by a subscale of the Toronto alexithymia scale; TAS), was correlated with the effectivity to increase amygdala activity (Young et al, 2017(Young et al, , 2014Zotev et al, 2011), which suggests that individuals with less symptoms of alexithymia might have better prerequisites to learn increasing their amygdala activity with neurofeedback.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, we highlight the explorative fashion of this finding and we stress that only the original data showed significant reductions. Nonetheless, our results are in line with a recent study showing that amygdala electrical fingerprint neurofeedback resulted in a larger reduction of alexithymia scores compared to a control group (Keynan et al, 2019). Conversely, neurofeedback studies to increase the amygdala response showed that the ability to identify or describe one's own emotions (as indicated by a subscale of the Toronto alexithymia scale; TAS), was correlated with the effectivity to increase amygdala activity (Young et al, 2017(Young et al, , 2014Zotev et al, 2011), which suggests that individuals with less symptoms of alexithymia might have better prerequisites to learn increasing their amygdala activity with neurofeedback.…”
Section: Discussionsupporting
confidence: 93%
“…Improvements in emotion regulation, assessed with the emotion-modulated startle, however, faded to the follow-up test; that is, some training effects did not persist for 6 weeks. Future studies must gain more stable effects, such as adding booster sessions or homework between sessions (Paret et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether immediate or delayed feedback is superior or whether they are equally effective is a matter of ongoing debate and there is only limited and as yet unclear evidence from a few comparative fMRI-neurofeedback studies (see Paret et al, 2019). In case of the noisier fNIRSneurofeedback, feeding back mean or median activity at the end of each block may avoid confusing participants due to noisy fluctuations of the feedback signal and may also be beneficial with regard to timing (see above).…”
Section: Feedback Presentationmentioning
confidence: 99%
“…Given the advantages of fNIRS over other neuroimaging modalities, this technique has been increasingly used as a tool for neurofeedback (Ehlis et al, 2018). During neurofeedback training, participants are trained to self-regulate their brain activity, generally with the ultimate goal of changing behavior or cognitive/emotional functions (for reviews see Paret et al, 2019;Sitaram et al, 2017;. Figure 0.2 (upper part) shows a typical fNIRS-neurofeedback setup.…”
Section: Introductionmentioning
confidence: 99%